2014
DOI: 10.1152/advan.00154.2012
|View full text |Cite
|
Sign up to set email alerts
|

Are all hands-on activities equally effective? Effect of using plastic models, organ dissections, and virtual dissections on student learning and perceptions

Abstract: This study investigated the impact of three commonly used cardiovascular model-assisted activities on student learning and student attitudes and perspectives about science. College students enrolled in a Human Anatomy and Physiology course were randomly assigned to one of three experimental groups (organ dissections, virtual dissections, or plastic models). Each group received a 15-min lecture followed by a 45-min activity with one of the treatments. Immediately after the lesson and then 2 mo later, students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
72
1
12

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 33 publications
6
72
1
12
Order By: Relevance
“…To a lesser extent, students reported that a lack of models and difficulty visualizing nervous system structures contributed to difficulties learning the nervous system. As being able to visualize anatomical structures through models or dissections has been shown repeatedly to benefit student learning (Kramer and Soley 2002, DeHoff et al 2011, Lujan et al 2013, Haspel et al 2014, Lombardi et al 2014, it does not come as a surprise that students would report this issue with regards to learning the nervous system. Indeed, undergraduate human anatomy students strongly favor the use of models when learning anatomy (Wright 2012, Anderton et al 2016, Shaffer 2016.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To a lesser extent, students reported that a lack of models and difficulty visualizing nervous system structures contributed to difficulties learning the nervous system. As being able to visualize anatomical structures through models or dissections has been shown repeatedly to benefit student learning (Kramer and Soley 2002, DeHoff et al 2011, Lujan et al 2013, Haspel et al 2014, Lombardi et al 2014, it does not come as a surprise that students would report this issue with regards to learning the nervous system. Indeed, undergraduate human anatomy students strongly favor the use of models when learning anatomy (Wright 2012, Anderton et al 2016, Shaffer 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Dissection was not only applicable to their training but it also helped them visualize the structures of the body. In addition, a variety of models (plastic, animal tissue, computer, etc) have been reported to be useful for learning human anatomy in several different contexts (Lombardi et al 2014) since models help students place objects or structures into forms that are more readily learned in a visual setting (Gilbert and Boulter 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Engagement with students is a highly valuable tool which can play a role in course completion (Hopper, 2016;Thalluri, 2016). Retention rates in science degrees tend to be poor (Lombardi, Hicks, Thompson, & Marbach-Ad, 2014), and student confidence and perceptions of science are often negative (Craker, 2006). In a university setting, a diversity in students' backgrounds results in variability amongst students in terms of their educational background and thus, learning styles.…”
Section: Student Perceptions To Undergraduate Teachingmentioning
confidence: 99%
“…It has also been suggested that younger students require a more entertaining and immersive approach in order to remain interested in course material (Miller et al, 2002). Since it has the potential to engage multiple learning styles, and create an environment where students are more likely to achieve meaningful learning, many have employed a multimodal learning environment in the hopes that enjoyment of the coursework will lead to a greater investment of time in studying the material, and consequently, academic success (Drake & Pawlina, 2014;Farkas, Mazurek, & Marone, 2016;Lombardi et al, 2014;Michael, 2006).…”
Section: Student Perceptions To Undergraduate Teachingmentioning
confidence: 99%
See 1 more Smart Citation